Credence goods, costly diagnosis, and subjective evaluation - Bester, Helmut; Dahm, Matthias (Wiley, 2018)
We study contracting between a consumer and an expert in a credence goods model when (i) the expert's choice of diagnosis effort is not observable, (ii) the expert might misrepresent his private information about the adequate treatment, and (iii) payments can depend only on the consumer’s subjective evaluation of treatment success. We show that the first--best solution can always be implemented if the parties' discount factor is equal to one; a decrease in the discount factor makes obtaining the first--best more difficult. The first--best is also always implementable if separation of diagnosis and treatment is possible.